1991
DOI: 10.1111/j.1365-2710.1991.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Risks and Benefits of Hormone Replacement Therapy

Abstract: Summary There is increasing awareness that the long‐term consequences of ovarian failure can be prevented or reduced with appropriate hormone replacement therapy (HRT). After the menopause, there is a rapid loss of trabecular bone resulting in a one in two lifetime risk of osteoporotic fracture. HRT prevents this bone loss and decreases the incidence of fracture. A minimum of 5 years treatment is recommended for significant benefit. Epidemiological evidence is accumulating that post‐menopausal oestrogen therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…However, the benefits of E2 replacement therapy (ERT) against post‐menopausal osteopenia are offset by the increased risk of breast and uterine cancers (Maggio, 1980; Steinberg et al ., 1991; Lobo, 1995; Langer et al ., 2003). Consequently, there is a growing interest in assessing the role of phytoestrogens in the prevention of post‐menopausal osteoporosis because of their apparent lack of the adverse effects commonly associated with ERT (Hillard et al ., 1991; Lien and Lien, 1996; Delmas, 1999; Carusi, 2000; Arjmandi, 2001; Ishimi, 2006; Coxam, 2008; Sharan et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, the benefits of E2 replacement therapy (ERT) against post‐menopausal osteopenia are offset by the increased risk of breast and uterine cancers (Maggio, 1980; Steinberg et al ., 1991; Lobo, 1995; Langer et al ., 2003). Consequently, there is a growing interest in assessing the role of phytoestrogens in the prevention of post‐menopausal osteoporosis because of their apparent lack of the adverse effects commonly associated with ERT (Hillard et al ., 1991; Lien and Lien, 1996; Delmas, 1999; Carusi, 2000; Arjmandi, 2001; Ishimi, 2006; Coxam, 2008; Sharan et al ., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies initially suggested a protective function of postmenopausal hormone replacement therapy (HRT) against heart disease with risk reductions of Յ35% to 50%. 2 But controlled clinical end point studies, such as Heart and Estrogen/progestin Replacement Study (HERS) and the recently terminated Women's Health Initiative (WHI) trial, reported no protective function of HRT consisting of conjugated equine estrogens plus medroxy-progesterone-acetate for the primary or secondary prevention of coronary artery disease. 3 In contrast, estrogen supplementation in animal models of human heart disease was mostly associated with beneficial hormone effects.…”
mentioning
confidence: 99%
“…The endocannabinoid system plays a modulatory role in several physiological processes, mainly in the brain [4,6,38] although also in peripheral processes such as the immune regulation [39], the cardiovascular system [40], the reproductive endocrine processes [41], and the control of energetic metabolism [42]. In the brain, endocannabinoids participate in processes such as the control of movement [43,44], learning and memory [45] and nociception [46], as …”
Section: Funtions and Therapeutic Potential Of The Endogenous Cannabimentioning
confidence: 99%